A Comparison of two different training methods for junior goalkeepers attending football schools - Astudillo Ganora, Ignacio Alejandro.; González Alvarado, Benjamín.; Guerra González, Maite.; Martínez Jofre, Catalina.; Lermanda Peña, Cristian Felipe.; Massone Bustamante, Macarena Paz. (AG Editor (Argentina), 2024)
Introduction: football is a popular sport in Latin-America and the rest of the world, the instruction of young football goalkeepers is key. Thus, the objective of this research is to compare two training methods for young goalkeeper trainees. Method: this study included 30 goalkeeper trainees, from 7 to 17 years old who were part of a football school in Santiago, Chile. The mobile app “My Jump” was used to calculate the ball’s flight time and hight in three vertical jump trials. Results: the results obtained in jump height present significant mean difference in the plyometric group of-4,005 (p= <0,0001. The control group did not show any significant change with a median of-0,6020 (p= 0,9865), in the plyometric group strength showed important changes with a mean difference of-4,064 (p= <0,0001). The results obtained for flight time present an important median in the plyometric group-35,92 (p= <0,0001). The control group remained unaltered with a mean difference of-5,875 (p= 0,8352), and in the plyometric group strength showed meaningful changes with a mean difference of-34,46 (p= <0,0001). However, no significant differences were observed between groups. Conclusion: the Authors recommend plyometrics training for goalkeeper trainees as it can improve jumping abilities, a vital condition for the sport.
Comparación de distintos métodos de entrenamientos en arqueros de escuelas de fútbol
Keywords: Physical therapy specialty; Resistance training; Physical therapy specialty; Resistance training; Fútbol; Arqueros (Fútbol)